Sex and Genotype Modulate the Dendritic Effects of Developmental Exposure to a Human-Relevant Polychlorinated Biphenyls Mixture in the Juvenile Mouse - Keil Stietz, Kimberly P.; Sethi, Sunjay; Klocke, Carolyn R.; de Ruyter, Tryssa E.; Wilson, Machelle D.; Pessah, Isaac N.; Lein, Pamela J. (Frontiers in Neuroscience, 2021)
While many neurodevelopmental disorders (NDDs) are thought to result from interactions between environmental and genetic risk factors, the identification of specific gene-environment interactions that influence NDD risk remains a critical data gap. We tested the hypothesis that PCBs interact with human mutations that alter the fidelity of neuronal Ca2+ signaling to confer NDD risk. To test this, we used three transgenic mouse lines that expressed human mutations known to alter Ca2+ signals in neurons: (1) gain-of-function mutation in ryanodine receptor-1 (T4826I-RYR1); (2) CGG-repeat expansion in the 5′ non-coding portion of the fragile X mental retardation gene 1 (FMR1); and (3) a double mutant (DM) that expressed both mutations. Transgenic and wildtype (WT) mice were exposed throughout gestation and lactation to the MARBLES PCB mix at 0.1, 1 or 6 mg/kg in the maternal diet. The MARBLES mix simulates the relative proportions of the twelve most abundant PCB congeners found in serum from pregnant women at increased risk for having a child with an NDD. Using Golgi staining, the effect of developmental PCB exposure on dendritic arborization of pyramidal neurons in the CA1 hippocampus and somatosensory cortex of male and female WT mice was compared to pyramidal neurons from transgenic mice. A multilevel linear mixed-effects model identified a main effect of dose driven by increased dendritic arborization of cortical neurons in the 1 mg/kg PCB dose group. Subsequent analyses with genotypes indicated that the MARBLES PCB mixture had no effect on the dendritic arborization of hippocampal neurons in WT mice of either sex, but significantly increased dendritic arborization of cortical neurons of WT males in the 6 mg/kg PCB dose group. Transgene expression increased sensitivity to the impact of developmental PCB exposure on dendritic arborization in a sex-, and brain region-dependent manner. In conclusion, developmental exposure to PCBs present in the gestational environment of at-risk humans interfered with normal dendritic morphogenesis in the developing mouse brain in a sex-, genotype- and brain region-dependent manner. Overall, these observations provide proof-of-principle evidence that PCBs interact with heritable mutations to modulate a neurodevelopmental outcome of relevance to NDDs.